PENGEMBANGAN GAME BERBASIS KEARIFAN LOKAL KALIMANTAN TENGAH UNTUK MENINGKATKAN NUMERASI SISWA SMP - Rahmat Winata; Rizki Nurhana Friantini; Dina Damiyanti Hidayat; Siti Dian Anugrah; Lisa Agustina; Christian Novan (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
This research is intended to design and develop an educational mathematics game based on the local wisdom of Central Kalimantan to improve junior high school students' numeracy, named GEMALOKA (Game Edukasi Matematika Lokal Kalimantan Tengah). This research employs a Research and Development (R&D) approach using the Thiagarajan 4D model, which includes the stages of Define, Design, Develop, and Disseminate. The participants in this study were seventh-grade students of SMP Negeri 6 Palangka Raya. The data were collected through expert validation sheets, student response questionnaires, and numeracy ability tests. The results showed that: (1) The GEMALOKA product was declared highly feasible based on media expert validation (92.6%) and material expert validation (90.6%); (2) The game was proven effective in improving students' numeracy, as indicated by a significant difference (sig. 0.043) between the experimental group (mean 74.93) and the control group (mean 66.88), as well as an N-Gain score of 0.4125 (moderate category); (3) Students’ responses toward the game were categorized as good (78.63%). Therefore, GEMALOKA is considered a valid, practical, and effective learning medium for enhancing students' numeracy skill.Keywords: educational game, mathematics, local wisdom, numeracy.